RELEVANSI PENDIDIKAN KARAKTER DALAM MEWUJUDKAN UNIVERSITAS NEGERI SEMARANG SEBAGAI UNIVERSITAS KONSERVASI (Faculty of Social Science, Universitas Negeri Semarang, 2015)
Semarang State University is a conservation university characterized by the excellence in Tri Dharma Perguruan Tinggi (three main function of highereducation), based on elevan conservation values, they are, religious, honest, smart, fair, responsible, care, tolerant, democratic, patriotism, tough and polite. The aim of this research is to: 1) describe the imlementation of character education based on Conservation and Competence-Based Curriculum of the 2012; 2) describe the relevance of character education in building Semarang State University as a conservation university. This is an evaluative research designed using CIPP (Context, Input, Process, and Product) Model. The rule in assessing the relevance of character education in the 8 faculties, they are, FIP, FBS, FIS, FMIPA, FT, FIK, FE, and FH, use the score of :1) 3,26-4= highly relevant, 2) 2,56-3,25= relevant, 3) 1,76-2,55= less relevant, dan 4) 1- 1,75= not relevant. Conservation-based character education is expected to produce graduates with good character that can contribute to the achivement of the vision of Semarang State University as a conservation university, that is a university that has a noble vision to keep, maintain and develop a cultural and natural environment. The output and outcome of the education in Semarang State University is the graduates that are prosperous, healthy and competitive. Research findings show that: 1) vision and mission reach the average score of 3.68 (highly relevant), 2) institutional policies reach the avergae score of 3,69 (highly relevant), 3) curriculum reach the average score of 3,50 (relevant), 4) student activities reach the score of 3,06 (relevant), and 5) facilities reach the average score of 3,50 (relevant). It can be concluded that most components of character education have been highly relevant in building Semarang State University as a conservation university, except the component of student (extracurricular) and facilities that only reach the average score of 3,26. The recommendation from this research is there is a necessity of assistance in integrating character education values in the extracurricular activities and student assistance in the level of university, faculty or department.